PRIORITY DETERMINATION OF SUBMARINE TYPE AS DEFENSE OF ARCHIPELAGIC WAR WITH FUZZY AHP METHOD AND BCR ANALYSIS - Dani Hutabarat; Udisubakti Cipto Mulyono; Ahmadi Ahmadi; Priyadi Hartoko (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
This thesis describes the application of the Fuzzy Analytical Hierarchy Process (Fuzzy AHP) approach and Benefit Cost Ratio (BCR) analysis in submarine selection. Submarines as Main Defenses System which are highly strategic in their procurement are directed at realizing a deterrence strategy and a strategy of balancing with state actors that have the potential to threaten the sovereignty of the Indonesian state. Apart from threats, the procurement of submarines also considers Indonesia's geographic constellation and the government's wishes, such as the interest of the minister of defense during working visits to countries that offer their submarines. The first step in procurement is to make an analysis in terms of selecting submarine alternatives, both analysis of information and identification of various important and interrelated requirements regarding data from submarine alternatives that will be selected later. Uncertainty from the government is a fuzzy'nes decision, so this condition can be resolved with the Fuzzy AHP approach and strengthened by BCR analysis, so that the results can provide a higher contribution. The results obtained from the Fuzzy AHP method are the priority order of selecting alternative submarines, namely Y-Class (0.398), W-Class (0.220), X-Class (0.191) and Z-Class (0.191). Where the results of the importance of the main criteria are sequential starting from the Strategic Requirement (Strareq) criteria of 0.409, Operation Requirement (Opsreq) of 0.318 and Technical Requirement (Techreq) of 0.273. Meanwhile, based on the BCR analysis, the Y-Class submarine was also selected with a BCR value of 1.512232936. Keywords: Fuzzy AHP method, BCR Analysis, Submarine Selection.